2017
DOI: 10.1017/s1754470x17000174
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for visual hallucinations: an investigation using a single-case experimental design

Abstract: There has been limited application of cognitive behavioural therapy (CBT) to the treatment of distressing visual hallucinations (VH) in people with psychosis. Preliminary research applying interventions to a novel presenting issue are enhanced by utilizing designs that allow strong inferences to be made about the effect of the intervention. Hence, this study aimed to measure change in appraisal, affect, and behaviour as a consequence of CBT VH, to improve understanding of the process of change. A multiple-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
9
1
1
Order By: Relevance
“…Whilst the questions were related to the distress of seeing the vision, clearly, future research with larger groups of participants (including Alzheimer Dementia, non-clinical populations) could consider if multimodality rather than diagnosis is most indicative of distress and conviction. Of course, other factors such as the content, frequency, persistence and appraisals of what it means to see visions (Dudley et al, 2012) may all also play a role in the distress and conviction reported (Thomson et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Whilst the questions were related to the distress of seeing the vision, clearly, future research with larger groups of participants (including Alzheimer Dementia, non-clinical populations) could consider if multimodality rather than diagnosis is most indicative of distress and conviction. Of course, other factors such as the content, frequency, persistence and appraisals of what it means to see visions (Dudley et al, 2012) may all also play a role in the distress and conviction reported (Thomson et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Tyrimų, aprašančių KET naudą regos haliucinacijoms, duomenys parodė, kad intervencijos metu dauguma pacientų tapo labiau kritiški savo simptomatikai (t.y. haliucinacijoms), pagerėjo jų afekto rodikliai, sumažėjo nepageidaujamo elgesio, sukelto pozityvių simptomų, apraiškos [7,8]. Analizuoti tyrimai rodo, jog šizofrenijos atveju svarbu ne tik siekti panaikinti simptomą (haliucinacijas), bet ir mokyti pacientą adekvačiai į jį reaguoti.…”
Section: Tyrimo Rezultataiunclassified
“… 82 , 83 Several psychotherapies initially developed for treating people with a primary psychotic disorder and auditory hallucinations (cognitive behavioral therapy, COMET, acceptance, and commitment) are also applied to older persons, 84 , 85 though less is known about the application of cognitive behavioral therapy for distressing visual hallucinations. 86 In some cases, adjustments need to be made when the cognitive resources of patients are limited. The essence of such therapies is that the patient learns that hallucinations are not a real-life threat, may have personal significance or meaning, or can safely be ignored.…”
Section: Management and Treatment Approachesmentioning
confidence: 99%